A Study on Assessing Government Size, the Composition of Public Spending on Education and Economic Growth in the USA - Choi, Wing Yee (Journal of Accounting, Business and Finance Research, 2020)
The paper aims to assess the effect of government size and the composition of public spending on education on economic growth in the USA. This study is quantitative, and the data has been gathered from the World Bank database for 60 years, from 1960 to 2019. The variables considered in the study include government size, GDP growth, inflation, FDI, GDP (current US), and government education expenditure (GEE) as a % of GDP in the USA. In terms of the analysis, the augmented Dickey–Fuller (ADF) has been used to determine the unit root. Moreover, the effect has been tested through the ADF and bounds tests. It has been determined from the analysis that GDP growth is dependent on the first lag, while there is a significant effect of government size and public expenditure on education on GDP. It was also found that the controlling effect of inflation is also significant. The results of this study are restricted to the USA. With respect to the implications, there is a huge significance of these results as the government of the USA can ensure economic growth while increasing educational expenses.